Historical and Pedagogical Prerequisites of Development of Preschool Education in Khmelnytskyi Region in 1950-1960-s - Gritsiuk, Tetiana (Pedagogical Discourse, 2013)
The results of exploration of historical and pedagogical prerequisites which were supporting progress of preschool education in 1950-1960-s in Khmelnytskyi region are highlighted in the article. The main tendencies of the development of pre-school education and factors influenced on this process are characterized. The reasons of success and problems in the pre-school education are analyzed. The main state documents which influenced the improvement of it content are analyzed. The development of the net of kindergardens, its structure, numbers of groupes, needs of children and parents are described. Statistics are given. The conclusion of article is an idea that experience of this period is important to decide the tasks of the modernization of pre-school education.